2021
DOI: 10.1186/s12877-021-02408-2
|View full text |Cite
|
Sign up to set email alerts
|

Towards personalized dementia care through meaningful activities supported by technology: A multisite qualitative study with care professionals

Abstract: Background Person-centred care is widely recognised as important for helping people with dementia maintain a sense of self and purpose in life – especially for those living in care facilities. Despite this, most care practices still adopt a medical approach in which physical needs are prioritized over psychosocial well-being. Addressing the need to find ways of promoting person-centred approaches in care, this study explored care professionals’ reflections on a novel, technological intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 44 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…Other studies were conducted in Australia ( n = 4), Canada ( n = 3), Hong Kong ( n = 1), and the US ( n = 7). Two articles included multi-national studies ( 56 , 57 ). Three research approaches were employed, including 12 quantitative, 11 qualitative, and 11 multi- or mixed-methods.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies were conducted in Australia ( n = 4), Canada ( n = 3), Hong Kong ( n = 1), and the US ( n = 7). Two articles included multi-national studies ( 56 , 57 ). Three research approaches were employed, including 12 quantitative, 11 qualitative, and 11 multi- or mixed-methods.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies reported interventions ( n = 22) which involved supporting caregiving dyads to participate in social activities (either supported by objects for shared attention or structured social sessions), cognitive and multisensory stimulation and self-management. Carer-provided stimuli for PLWD was a central means to support social participation, either through cognitive stimulation therapy (CST) ( 66 , 67 ) or in dedicated rooms, the latter including multisensory stimulation to improve caregiving in institutional settings through meaningful social interactions in the caregiving dyads ( 57 , 68 ). Bemelmans et al ( 60 ) reported on an intervention involving the social pet robot, PARO, to elicit social engagement and facilitate interactions between dyads.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations